Kolaborasi Stakeholder dalam Pengembangan Pariwisata Berkelanjutan di Desa Wisata Pandean Kecamatan Dongko Kabupaten Trenggalek - Afifah Dina Fatin; Florensia Devina; Moh Musleh (Jurnal Administrasi Publik, 2024)
Pandean Tourism Village is a tourist village located in Dongko District, Trenggalek Regency. Pandean Village Trenggalek is one of the best tourist villages in Indonesia. This is evidenced by the determination of the top 50 Indonesian Tourism Village Award (ADWI) 2022 by the Ministry of Tourism and Creative Economy (Kemenparekraf). Pandean village is a mountainous area with cool air, crossed by a river with exotic rock contours. The development of the tourism industry currently requires the involvement of various stakeholders from various circles. The role of stakeholders is aligned with their roles and responsibilities so that the results achieved can run optimally. Collaboration is a process where stakeholders interact and negotiate, jointly creating a rule and structure that can regulate their relationships and ways of acting or deciding on issues that are brought up. By applying the concept of collaboration, tourism potentials will be more developed with various innovations. This research aims to find out who is involved in stakeholder collaboration for the development of Pandean tourism village. This research uses a qualitative method with a case study approach. The theory used is according to Calzada (2016). Data collection techniques used interviews, documentation, and observation. The results showed that stakeholder collaboration in the development of Pandean Tourism Village includes five actors who play a role, namely the government, business actors, the community or community, academics, and social media.